The nexus between the failure of African governance and poor leadership styles 1980-2015 - Chimwango, Promise Vimbisoyashe (Midlands State University, 2020)
This study sought to discover the relationship between poor policies and poor leadership styles basing on the case of Zimbabwe. The task being to investigate the leadership style that govern Zimbabwe and exhibiting how it has affected governmental policies. The study adopted a qualitative design to investigate the effects of leadership style upon policies. From the discovery the study revealed the government of Zimbabwe is democratic in paper but its reality is autocracy. The outcome was based on interviews, peer discussions and also document analysis. Finally, the study recommended for the government to eliminate autocratic tendencies by adopting a genuine democracy.